2019
DOI: 10.1002/admi.201901373
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Layer‐by‐Layer Films of Poly(acrylic acid)–Gentamicin Complexes with a Combined Burst and Sustainable Release of Gentamicin

Abstract: There is an urgent need for the development of effective antibacterial coatings to cope with more and more resistant bacterial strains in medical environments, and particularly to prevent nosocomial infections following bone implant surgery. Polyelectrolyte multilayers (PEMs) based on poly‐l‐lysine (PLL) and complexes of poly(acrylic acid) (PAA) and gentamicin have been fabricated here applying the layer‐by‐layer (LbL) technique. Complexes are prepared by mixing PAA and gentamicin solutions in 500 × 10−3 m NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…In future work, the developed here nanofibrillar structures can be functionalized by different essential functional components, for example, pectins, [ 88,89 ] chitosan, [ 90 ] gentamicin, [ 91 ] which can be used to regulate environment and antibacterial properties. [ 92,93 ] Alternatively, nanoparticle functionalization of the surfaces would enable remote release capabilities, [ 94 ] while functionalization with anisotropic structure would permit mechanical properties control.…”
Section: Resultsmentioning
confidence: 99%
“…In future work, the developed here nanofibrillar structures can be functionalized by different essential functional components, for example, pectins, [ 88,89 ] chitosan, [ 90 ] gentamicin, [ 91 ] which can be used to regulate environment and antibacterial properties. [ 92,93 ] Alternatively, nanoparticle functionalization of the surfaces would enable remote release capabilities, [ 94 ] while functionalization with anisotropic structure would permit mechanical properties control.…”
Section: Resultsmentioning
confidence: 99%
“…29 Implantable biomaterials with antibacterial performances can inhibit bacterial infection, and thus maintain long-term stability of the implants. 30 Previous studies have shown that -SO 3 H groups on biomaterials could reduce bacterial adhesion and prevent bacteria from biofilm formation, showing antibacterial performances. 31 In addition, sulfonation of PEEK caused a negatively charged surface, which produced a repulsive force between the negatively charged membranes of bacteria, thereby hindering bacteria attachment.…”
Section: Discussionmentioning
confidence: 99%
“…The multilayer is formed on top of titanium discs, and they obtained an initial burst release of TC, which has an antibacterial effect against Porphyromonas gingivalis [ 100 ]. A. Escobar et al [ 101 ] prepared an antibacterial coating on titania based on the formation of complexes of PAA and gentamicin, which are assembled with poly lysine (PLL) ( Figure 3 A). The multilayer formation followed an exponential growth ( Figure 3 B) and was demonstrated to be effective in preventing the proliferation of S. aureus ( Figure 3 C) [ 101 ].…”
Section: Lbl For Antibiotic Encapsulationmentioning
confidence: 99%
“…A. Escobar et al [ 101 ] prepared an antibacterial coating on titania based on the formation of complexes of PAA and gentamicin, which are assembled with poly lysine (PLL) ( Figure 3 A). The multilayer formation followed an exponential growth ( Figure 3 B) and was demonstrated to be effective in preventing the proliferation of S. aureus ( Figure 3 C) [ 101 ]. Only four layers of PAA-gentamicin complexes and PLL are needed to produce a film with a superior antibacterial performance as compared to that reported elsewhere [ 90 ] The release of gentamicin shows a two-step profile; an initial burst release followed by a prolonged release lasting more than a month.…”
Section: Lbl For Antibiotic Encapsulationmentioning
confidence: 99%
See 1 more Smart Citation